Validação de instrumento para identificação de variáveis que influenciam na satisfação de usuário de sistemas de informação - Siqueira, Nilson Amaury (2010)
It‟s very interesting demonstrates the needs of organizations, whether they private or public, of mechanisms that ensure information quality and quick access. Such mechanisms, among other functions, shall ensure the security and availability of information to the user. This is the work of information systems (SI): collect (or recover), process, store and distribute information for decision-making, coordination and control of an organization. In the light of its importance to the success of organizations, the study of the use of information systems has been a lot of attention for at least three decades. Understand the factors that necessitate the use of information systems is to establish relationships between behavior and attitudes of individuals, for example, the effort noticed and performance against technology, adjust this with the task to be performed and the degree of satisfaction that user front SI available. As a result, this research has focused study of motivational factors that impact the technology. Therefore, the main object of this work is to investigate whether or not respect/connection among constructs "Perceived effort", "performance", "Adequacy between task and technology" and "User satisfaction" in an institution of higher education (IES). The character was a case study. Were applied 167 questionnaires with public IES servers that actually use SI to perform their tasks. The results cited for identification of the variables that influence in user satisfaction of SI through the process of quantitative analysis developed in this work.